2010
DOI: 10.1111/j.1601-5037.2009.00412.x
|View full text |Cite|
|
Sign up to set email alerts
|

Challenging parents’ myths regarding their children’s teething

Abstract: This study shows a common lack of knowledge about teething among parents. Parents should be better educated about the teething process and the proper management of teething troubles by the dental health care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
6
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 14 publications
6
62
6
9
Order By: Relevance
“…14 (38.9%), but lower than that found by Owais et al 10 (84.9%). The timing of eruption of the deciduous incisors (6-12 months) coincides with the reduction in circulating maternal humoral immunity and the establishment of a child's humoral immunity.…”
Section: Discussioncontrasting
confidence: 52%
“…14 (38.9%), but lower than that found by Owais et al 10 (84.9%). The timing of eruption of the deciduous incisors (6-12 months) coincides with the reduction in circulating maternal humoral immunity and the establishment of a child's humoral immunity.…”
Section: Discussioncontrasting
confidence: 52%
“…9,10 Our finding showed that 34 % of mothers falsely believed that fever was associated with teething; this was in accordance with that of Wake et al 7 , who found that parents believed that teething causes fever, pain, irritability, sleep disturbance, and drooling saliva. The proportion of mothers with this false belief in the present study was higher than that found by Feldens et al 10 (38.9%), but lower than that found by Owais et al 8 (84.9%). The timing of eruption of the deciduous incisors (6-12 months) coincides with the reduction in circulating maternal humoral immunity and the establishment of a child's humoral immunity.…”
Section: Resultscontrasting
confidence: 56%
“…Recent studies have suggested that tooth eruption could be accompanied by different benign symptoms, such as increased salivation, irritability, loss of appetite for solid foods, and rise in body temperature. [3][4][5][6][7][8][9][10][11] Moreover, the eruption of primary teeth has been assumed among parents to be associated with behavioral and systemic changes. [12][13][14][15][16][17] The period of time that tooth eruption occurs can be very frustrating and stressful for parents, especially when it happens to their first offspring.…”
mentioning
confidence: 99%